(untitled) (Samarra Journal of Pure and Applied Science, 2026)
In this study, zinc oxide nanoparticles were prepared using Tradescantia spathacea leaves extract and characterizing it with both (XRD) and (EDX) and working on mixing (3 wt%) of the mixture Cetyltrimethylammonium bromide/Sodium Dodecyle Sulphate (CTAB/SDS) as a surfactant with ZnONPs as a tertiary mixture, with the aim of making CTAB and SDS more effective and with fewer damages by employment lower doses of them. effect of different concentrations of the zinc oxide nanoparticle solution on the ratio (2:8) was studied the most viscous of the binary mixtures of surfactants (SDS/CTAB), which is classified as containing more micelles than in other mixing ratios. The results showed that the highest value (2705.223 Pa.s×102) was at a temperature of 298 K, and the lowest value (1.506897 Pa.s×102 ) was at a temperature of 323 K, also showed that ∆Go values ​​generally increased with increasing temperature and the higher concentration of nanomaterial gave lower ∆Go values. In addition, it was observed that the mixing exothermic process and the entropy change was negative, meaning that the system is in a state where the arrangement of molecules is regular.